Disruption and Maintenance: New Technologies and Dynamics of Access and Display - Alvarez, Maria (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
The dissertation examines the constrains and affordances of new technologies of display in relation to established paradigms of access and display within the culture and heritage sphere. It posits that new technologies of display structure and are structured by dynamics of access and display; positioned in the production of knowledge, circulation, and mediation. The research question is explored through: a primary theoretical framework made up of analysis of past literature on discourse, display, and new technologies; and three case studies each exploring a different technology utilized for the display and circulation of knowledge within the culture and heritage context. These case studies involve: Van Gogh: The Immersive experience (studying immersive technologies), Europeana.eu (studying platforms and digitalization processes), and Digital Benin ( studying database and interface design). This dissertation utilizes interviews with project team members to gain insights on project production processes, practical challenges of the technologies, and ultimate project objectives. Through these case studies this dissertation traces a form of de facto classification of the technologies adopted by different stakeholders within the sector; classified by organizational purpose, technology affordances, and audience demands. This methodology allows this dissertation to reinforce and track similar themes throughout while also opening up new avenues for the exploration of specific technologies within the realm of culture and heritage. The results show that new technologies of display are not inherently disruptive to established dynamics of access, display, and discourse within the culture and heritage sphere; instead impact is dependent on specific technology implementation methods and informed by these established structures.
Keywords: Digital Humanities and Culture